Wide-Pulse High-Frequency Neuromuscular Electrical Stimulation Evokes Greater Relative Force in Women Than in Men: A Pilot Study - Xin Ye; Nathan Gockel; Daniel Vala; Teagan Devoe; Patrick Brodoff; Victor Gaza; Vinz Umali; Hayden Walker (MDPI AG, 2022)
This study aimed to examine the potential sex differences in wide-pulse high-frequency neuromuscular electrical stimulation (WPHF NMES)-evoked force. Twenty-two subjects (10 women) completed this study. Prior to the stimulation, the visual analogue scale (VAS) for discomfort and the rating of perceived exertion (RPE) were measured, followed by the isometric strength of the dominant elbow flexor muscles. The subjects then completed ten, 10-s on 10-s off WPHF NMES (pulse width: 1 ms, frequency: 100 Hz) at maximum tolerable intensities. The subjects' RPE was recorded after each set, and the VAS was measured following the last stimulation. The stimulation induced significant increase in discomfort for both sexes, with women having greater discomfort than men (men: 22.4 ± 14.9 mm, women: 39.7 ± 12.7 mm). The stimulation amplitude was significantly greater in men than in women (men: 16.2 ± 6.3 mA, women: 12.0 ± 4.5 mA). For the evoked force, only the relative NMES-evoked force was found greater in women than in men (men: 8.96 ± 6.51%, women: 17.08 ± 12.61%). In conclusion, even at the maximum tolerable intensity, WPHF NMES evoked larger relative elbow flexion force in women than in men, with women experiencing greater discomfort.